PENGARUH INFLASI DAN SUKU BUNGA TERHADAP RETURN SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN MANUFAKTUR TAHUN 2018-2019 - Durrotul Yatimah; Maslichah Maslichah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
This study aims to determine (1) Knowing the effect of inflation on stock returns in manufacturing companies in 2018-2019. (2) Knowing the effect of interest rates on stock returns in manufacturing companies in 2018-2019. (3) Knowing the effect of profitability on stock returns in manufacturing companies in 2018-2019. (4) Knowing the effect of Inflation on Stock Returns with Profitability being a moderating variable in Manufacturing companies in 2018-2019. (5) Knowing the effect of interest rates on stock returns with profitability being a moderating variable in manufacturing companies in 2018-2019. This research uses quantitative research methods. The population used is manufacturing companies listed on the Indonesian Stock Exchange (IDX) in the 2018-2019 period. The sampling technique used was purposive sampling, so the number of samples was 70 companies. The results of this study indicate that (1) Partially Inflation has no significant effect on stock returns. This is evidenced by the Inflation significance value of 0.301, where the significance value is greater than 0.05. (2) Partial interest rates do not have a significant effect on stock returns. This is evidenced by the significance value of the Interest Rate of 0.680, where the significance value is greater than 0.05. (3) Partially profitability has a significant effect on stock returns. This is evidenced by the significance value of the Interest Rate of 0.026, where the significance value is smaller than 0.05. (4) Profitability is not able to moderate the relationship between Inflation and stock returns. This is evidenced by the significance value of the multiplication result of the Inflation variable with the profitability of 0.362, where the significance value is greater than 0.05. (5) The results showed that profitability was not able to moderate the relationship between interest rates and stock returns. This is evidenced by the significance value of the multiplication result of the Inflation variable with the profitability of 0.447, where the significance value is greater than 0.05. Keywords: Inflation, Interest Rate, Profitability, and Stock Return